Real time motorcycle image detection and analysis - Mat Nong, Mohd Ali; Mohd Sidek, Roslina; Osman, Rosiah; Sabil, Suzila; Md Yusof, Juraina (Electrochemical Society, 2018)
This research investigated image tracking and edge detection for motorcycle in various lighting and weather conditions. The capability in different resolution and threshold level also evaluated. Comparison between hardware and software implementation of edge detection also been made. Develop framework showed great accuracy is segmentation of plate number from motorcycle image in daylight condition compared to rainy daylight and night condition. The aim of this project is to develop framework for motorcycle image detection and recognize for traffic offender. Analysis with histogram level and contrast stretching method showed performance in hardware is improved rather than software.